Kelangkahan minyak goreng pada masyarakat dalam perekonomian Indonesia memiliki dampak pada pedagang kecil - Liasari, Nancy Herninda (Maliki Interdisciplinary Journal, 2024)
The impact of the shortage of vegetable oil on small traders in the Indonesian economy. The shortage of Indonesian vegetable oil in 2022 will have a significant impact on small traders, especially those operating in the culinary sector. Rising prices and shortages of vegetable oils will have the following impacts: Increased production costs: Small traders will have to pay higher costs to buy vegetable oils, thereby reducing their profits. Decline in sales: Cooking oil is expensive and scarce, limiting consumer purchases, leading to a decline in sales for small retailers. Menu changes: Small traders are forced to change their menus by using cheaper ingredients or by reducing the proportion of food they sell. Business Closure: In some cases, small and medium businesses that are unable to survive these conditions are forced to close their operations. The shortage of vegetable oils not only impacts small traders but also the wider community. This shows that price stability and availability of basic commodities such as vegetable oil are very important to maintain economic stability and social welfare in Indonesia.